Medical Imaging 2023: Image Processing 2023
DOI: 10.1117/12.2653947
|View full text |Cite
|
Sign up to set email alerts
|

Comparing voxel- and feature-wise harmonization of complex graph measures from multiple sites for structural brain network investigation of aging

Abstract: Complex graph theory measures of brain structural connectomes derived from diffusion weighted images (DWI) provide insight into the network structure of the brain. Further, as the number of available DWI datasets grows, so does the ability to investigate associations in these measures with major biological factors, like age. However, one key hurdle that remains is the presence of scanner effects that can arise from different DWI datasets and confound multisite analyses. Two common approaches to correct these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Alzheimer's Disease Neuroimaging Initiative (ADNI) 16 and National Alzheimer's Coordinating Center (NACC) 17 incorporates data from multiple scanner vendors and protocols, Open Access Series of Imaging Studies (OASIS3) 18 includes multiple protocols, and Baltimore Longitudinal Study of Aging (BLSA) 19 has data from distinct scanning locations. These site specifications may introduce significant confounding differences in DWI and downstream connectomic analysis [20][21][22][23] . Vollmar et.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alzheimer's Disease Neuroimaging Initiative (ADNI) 16 and National Alzheimer's Coordinating Center (NACC) 17 incorporates data from multiple scanner vendors and protocols, Open Access Series of Imaging Studies (OASIS3) 18 includes multiple protocols, and Baltimore Longitudinal Study of Aging (BLSA) 19 has data from distinct scanning locations. These site specifications may introduce significant confounding differences in DWI and downstream connectomic analysis [20][21][22][23] . Vollmar et.…”
Section: Introductionmentioning
confidence: 99%
“…Schilling et al showed that fiber bundle shape and microstructure analysis was affected by scanner manufacturer, acquisition protocol, diffusion sampling scheme, diffusion sensitization and overall bundle processing workflow 22 . Joint datasets of complex network measures in Newlin et al 23 and Onicas et al 25 show that modularity, global efficiency, clustering coefficient, density, characteristic path length, small worldness, and average betweenness centrality have significant differences due to protocol and scanner vendor. Thus, there is a clear need to account for these site biases in connectivity analyses, or "harmonize" [26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…There are a growing number of multi-center studies that span multiple scanner, and acquisition protocols, or "sites". Unfortunately, these site specifications introduce significant confounding differences in images and downstream analysis such as diffusion tensor imaging (DTI) metrics and connectomics [11]- [15]. Thus, there is a growing number of methods designed to reduce site-related differences whilst preserving biological variability, or "harmonization" [16], [17].…”
Section: Introductionmentioning
confidence: 99%